Comparison of Ideal Traction Hyperbola Curves with Matlab-Simulink in Vehicles - Faruk Emre Aysal; Hüseyin Bayrakçeken; Hicri Yavuz (International Journal of Automotive Science and Technology, 2020)
The gearbox is part of the powertrain that transmits movement from the engine to the wheels. Gears, shafts and auxil-iary systems are used in Gearboxes. By using these systems, it is possible to control the movement of the vehicle at the desired tractive effort and vehicle speed in different gear ratios as well as in different direction situations. To increase vehicle performance, it is necessary to obtain curves close to the ideal traction hyperbola.